PHARMACY EDUCATION IN INDIA: CURRENT STANDARD, ADMISSION CRITERIA AND REGULATION - B. BHUYAN (International Journal of Pharma and Bio Sciences, 2013)
The formal pharmacy education in India started long ago in 1937. But in India it turned to be a mostly industry oriented program. In India AICTE and PCI regulates all the education programs. The minimum qualification required for becoming a pharmacist is the Diploma in pharmacy (D. Pharm). But its course contents can be considered to need a revision by PCI in the aim of modification to comply with the present society needs. B. Pharm and M. Pharm courses are industry oriented and newly introduced PharmD program is aimed at pharmacy practice. For taking admission into D. Pharm, B. Pharm or PharmD program one can apply after successful completion of the Higher Secondary in Science stream and pharmacy graduates can take admission in M. Pharm program. In this article a trial is made to describe the present situation of education including course contents, standard, regulation and admission criteria etc.